Disease control and Ebola in West Africa: a qualitative evidence synthesis - Bell, AJ; Van Bortel, T; Chng, NR; Wells, V (University of New South Wales, 2022)
Aims: The West African Ebola Virus Disease (EVD) outbreak of 2014-2016 was the most disastrous EVD epidemic in history. We aimed to investigate and provide unique theoretical insights which could help inform future responses to EVD outbreaks.